Equality and diversity in secondary schools: teachers' agentic and constrained enactments of the curriculum (UCL Press, 2022)
In England educators have been concerned about ensuring equality and diversity in education due to ever-diversifying school populations, who find themselves positioned as outsiders to England's National Curriculum. This article explores the accessibility and limitations of the curriculum from the perspective of ten secondary school teachers in nine different subjects in inner city state schools. We begin by examining the participants' goals and aims when enacting the curriculum to make it accessible to all students. However, the prescriptive nature of the curriculum in most subjects makes this task challenging. We then examine how participants perceived that they enabled students' access to the curriculum and the challenges encountered. We focus on art and English to highlight the different spaces to enact equality and diversity within the curriculum. In the nonprescriptive art curriculum, teachers choose their own resources and themes, allowing for greater creativity and cultural inclusivity. In contrast, in the English curriculum, teachers find the process of equalising and diversifying the curriculum difficult, particularly at Key Stage 4, due to the high status of the subject. To conclude, we argue that the more prescriptive a curriculum subject is, the more difficult it is to make it equal, diverse and inclusive of everyone.